Delphi Technique in Health Sciences: A Map - Niederberger, Marlen; Spranger, Julia (Frontiers in Public Health, 2020)
Objectives: In health sciences, the Delphi technique is primarily used by researchers when the available knowledge is incomplete or subject to uncertainty and other methods that provide higher levels of evidence cannot be used. The aim is to collect expert-based judgments and often to use them to find identifya consensus. In this map, wWe provide an overview of the fields of application for Delphi techniques in health sciences in this map and discuss the processes used and the quality of the findings. We use systematic reviews of Delphi techniques for the map, summarize their findings and examine them from a methodological perspective. Methods: Twelve systematic reviews of Delphi techniques from different sectors of the health sciences were identified and systematically analyzed. Results: The twelve systematic reviews show, that Delphi studies are typically carried out in two to three rounds with a deliberately selected panel of experts. A large number of modifications to the Delphi technique have now been developed. Significant weaknesses exist in the quality of the reporting. Conclusion: Based on the results, there is a need for clarification with regard to the methodological approaches of Delphi techniques, also with respect to any modification. Criteria for evaluating the quality of their execution and reporting also appear to be necessary. However, it should be noted that we cannot make any statements about the quality of execution of the Delphi studies but rather our results are exclusively based on the reported findings of the systematic reviews.